The Influence of Tax Incentives and Financial Conditions on Tax Compliance Registered at KPP Pratama Tabanan - Ni Wayan Dian Irmayani; Agus Putu Sepriyadi; Putu Diah Krisna Junitasari; Gusti Ayu Putu Eka Dewi Prihantari (International Journal of Integrative Sciences, 2023)
The tax industry is a substantial source of state revenue. The enhancement of tax compliance is a pivotal determinant in boosting the tax sector's revenue, thereby prompting the government, by means of its Directorate General of Taxes (DGT), to persist in its efforts to improve tax compliance. The present research endeavors to ascertain the impact of tax incentives and financial conditions on tax compliance. The present study was executed on individuals who have enrolled as taxpayers and are currently registered under the administration of the KPP Pratama Tabanan. The methodology employed for gathering data encompassed the utilization of questionnaires, documentation, and observation techniques. The analytical methodology utilized in this study adopts a multifaceted approach involving the employment of multiple linear regression analysis. This commences with the evaluation of the research instrument and the application of classical assumption testing. The findings indicate that tax incentives and financial circumstances exerted a favorable and noteworthy influence on tax conformity among taxpayers who had registered with KPP Pratama Tabanan